The Effectiveness of Coaching-Based Academic Supervision in Improving Teacher Performance: A Case Study at SD Negeri 1 Sedan - Yanti Yuni Astuti; Ngurah Ayu Nyoman; Muhammad Prayito (Journal of Educational Sciences, 2026)
Improving teacher performance remains a central priority in efforts to enhance instructional quality in Indonesian primary schools. Conventional supervision practices, which often focus on administrative compliance, have been criticized for their limited impact on classroom instruction. In response, coaching-based academic supervision has emerged as a more empowering and reflective approach to professional development. This study examines the effectiveness of coaching-based academic supervision in improving teacher performance at SD Negeri 1 Sedan. Using a qualitative descriptive design, data were collected through interviews, observations, and documentation, then analyzed using an interactive model of data condensation, data display, and conclusion drawing. The findings show that coaching enables principals to identify teacher needs through data-driven analysis, establish flexible supervision schedules, and set clear instructional performance indicators. During implementation, coaching fosters reflective dialogue, constructive feedback, and collaborative problem-solving, leading to improved lesson planning, classroom interaction, and pedagogical decision-making. Evaluation is conducted through joint reflection and analysis of observation results, forming the basis for continuous follow-up coaching. The study concludes that coaching-based supervision offers a more holistic and impactful model than traditional supervision, although it requires strong coaching skills and adequate time allocation. Future studies should examine long-term effects across diverse school contexts.